Trajectory tracking control for electro-optical tracking system based on fractional-order sliding mode controller with super-twisting extended state observer. (November 2021) - Zhou, Xinli; Li, Xingfei
Abstract: This paper investigates a trajectory tracking control scheme for electro-optical tracking systems subject to friction and other nonlinear disturbances. The proposed approach is based on a super-twisting extended state observer (ESO) and a fractional-order nonsingular terminal sliding mode (FONTSM) with a switching-type reaching law. The novel hybrid control scheme exhibits the following advantageous characteristics. First, the extended state observer injected with a super-twisting algorithm is capable of simultaneously estimating the friction and other nonlinear disturbances without detailed knowledge of the precise friction and disturbance models. Second, the FONTSM surface enhances the control accuracy and robustness, and provides a more flexible controller structure than its integer counterpart. Third, a novel switching-type reaching law is utilized to achieve fast response, constraining chattering in the system. Additionally, the finite-time convergence of the adopted ESO and the finite-time stability of the control system are demonstrated based on the rigorous Lyapunov criteria. Finally, the effectiveness of the proposed hybrid control scheme is demonstrated for an electro-optical tracking system via trajectory tracking experiments. Highlights: Propose a novel super-twisting ESO to estimate friction and other nonlinear disturbances. Propose a novel FONTSM controller with a switching-type reaching law. Validate the finite-time convergence of the super-twisting ESO and the closed-loop system. Demonstrate the superiorities of the novel hybrid control scheme via experiments.